Mild and moderate dyskaryosis: can women be selected for colposcopy on the basis of social criteria?. Issue 6845 (11th July 1992) - Anderson, D. J.; Flannelly, G. M.; Kitchener, H. C.; Fisher, P. M.; Mann, E. M.; Campbell, M. K.; Templeton, A.
Abstract : OBJECTIVE--To describe the distribution of cervical intraepithelial neoplasia grades among women with mild and moderate dyskaryosis after a single cervical smear and to determine whether social criteria could help identify women who are at increased risk of grade II or III disease. DESIGN--Cross sectional analysis within a randomised prospective study. Subjects had a repeat smear, a colposcopic examination, and an excision biopsy of the transformation zone. In addition, women were asked to complete a social questionnaire. SETTING--Colposcopy clinic, Aberdeen. SUBJECTS--228 women with a single smear test showing mild or moderate dyskaryosis. MAIN OUTCOME MEASURES--Histology, age, sexual and contraceptive history, cigarette smoking. RESULTS--159 (70%) women had cervical intraepithelial neoplasia grades II or III. Among current smokers the prevalence of grade II and III disease was higher in women who smoked greater than or equal to 20 cigarettes a day (84%) than among those who smoked less (66%; p less than 0.04). Women with more than one sexual partner also had a higher prevalence (75%) than women with only one partner (50%; p = 0.0028). Use of oral contraceptives and younger age were not significantly associated. The prevalence of grade II or III disease was up to 66% in the lower risk groups. CONCLUSIONS--Because of the high prevalence of cervical intraepithelial neoplasia grades II and III in both the high and the low risk groups social factors are not useful for selecting women with mild or moderate dyskaryosis for either early referral to colposcopy or cytological surveillance.